A wide environmental analysis of beekeeping systems through life cycle assessment: key contributing activities and influence of operation scale - Leonardo Vásquez-Ibarra; Alfredo Iriarte; Pablo Villalobos; Francisco Meza Rengel; Ricardo Rebolledo-Leiva; Lidia Angulo-Meza; Marcela C. González-Araya (International Journal of Agricultural Sustainability, 2022)
Agri-food has become an economic sector under increasing pressure in order to support food demand and decrease environmental impacts. One valuable methodology to evaluate environmental impacts is life cycle assessment (LCA), which has been employed in different economic sectors, however, beekeeping has been scarcely explored. In this context, this article investigates the environmental profile of 31 Chilean beekeeping systems reporting 15 environmental impact categories with a cradle to gate approach. In this way, this study identifies key contributing activities, variability in the environmental impacts, differences among operation scales, and provided efficient management practices for policy-makers. To the best of our knowledge, this is the first study that conducts a wide environmental analysis of beekeeping systems through LCA. The results show that feeding is the most impacting activity in all categories, followed by hives transport. Otherwise, medication, consumption of disposable inputs and honey extraction contribute less than 5% in average across all categories. Regarding the operation scale, the results suggest that small-scale beekeepers have the lowest environmental performance. Otherwise, medium-scale beekeepers have better environmental performance than the large-scale ones, depending on the environmental impact category evaluated. Finally, managerial practices in order to achieve sustainable honey production are provided.